Respuesta :
Answer:
[tex]x = - 3 \: and \: y = - 11[/tex]
Step-by-step explanation:
L
[tex]since \: y = 2x - 5(equation \: 1) \: \\ [/tex]
[tex]substitute \: for \: y \: in \: equation \: 2 \: (6x + 7 = y)[/tex]
[tex]6x + 7 = y \\ 6x + 7 = 2x - 5 \\ collect \: like \: terms \\ 6x - 2x = - 5 - 7 \\ 4x = - 12 \\ x = \frac{ - 12}{4} \\ x = - 3[/tex]
[tex]substitute \: for \: x in \: equation \: 1[/tex]
[tex]y = 2x - 5 \\ y = 2( - 3) - 5 \\ y = - 6 - 5 \\ y = - 11[/tex]
Answer:
[tex]y = 2.x = \frac{1}{11} [/tex]
Step-by-step explanation:
[tex] \binom{x - 56x + 7 = y}{y = 2} [/tex]
_______________________
1. Substitute y = 2 :
[tex](x - 56x + 7 = 2)[/tex]
2. Simplify :
[tex]( - 55x + 7 = 2)[/tex]
3. Isolate x for [tex]( - 55x + 7 = 2) : x = \frac{1}{11} [/tex]
4. The solution of the system of equations are :
[tex]y = 2.x = \frac{1}{11} [/tex]